Physical and chemical characterization of umbugueleira fruits (Spondias sp.) in the semi-arid state of Pernambuco (Research, Society and Development, 2021)
Native fruits came to be seen as an excellent alternative to the Northeast region, especially the umbugueleira. The fruits of spondias sp. are appreciated by consumers due to bioactive compounds, which has favored adding value to products and increasing family income. However, research on fruit quality is necessary and important, since the results obtained are still inconsistent. In view of the above, the objective of this work was to evaluate the physical and chemical characteristics of umbugueleira fruits in the semiarid state of Pernambuco. The work was carried out at the Chemistry Laboratory of the Serra Talhada Academic Unit of the Federal Rural University of Pernambuco. Fruit was used in the mature stage, with yellow peel coloration. The physical and chemical characterization of fruit mass, fruit shape, pulp yield, peel and seed, soluble solids (oBrix), titratable acidity, pH, and maturation index (SS/TA ratio), respectively, were selected. Twenty replicates of 10 fruits were used. The data were obtained through descriptive parameters and determination of Pearson's linear correlation coefficients. Based on the results, it was observed that the fruits with higher length and diameter had higher pulp yield. The SS/TA ratio showed a higher correlation with soluble solids than fruit acidity, being more representative than the isolated measurement of these parameters, since the maturation index is one of the most appropriate ways to evaluate the flavor.